The consequences of indirect taxation on consumption in Nigeria - Cordelia Onyinyechi Omodero (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
This research tests the consequences of Nigeria's indirect taxes on consumption. There are two reasons why the government imposes taxes on goods and services in Nigeria. The primary purpose is to produce income for the smooth running of the administration. Another silent reason is to discourage the ingestion of prohibited products and services, and that is through customs and excise duties (CED). This study assesses both Value Added Tax (VAT) and CED to determine their effects on consumption using various econometric tools, such as trend analysis, pairwise Granger causality tests, unrestricted co-integration rank test, least squares technique, and data that cover the period from 2005 to 2019. The results indicate that VAT insignificantly but positively influences consumption, while CED has a considerable auspicious influence on use. This result shows that VAT imposition on merchandises and services is discouraging the absorption of specific foodstuffs and services and allowing the operation of informal economic activities to thrive in Nigeria. However, CED charges do not reduce the use of certain illegal products purposely taxed to discourage their consumption. This study recommends a reduction in the prices of food items and services to enable consumers to increase their patronage, while the products that attract CED but are harmful should be banned entirely. Thus, offenders should be allowed to face the wrath of the law.
Keywords: 650; consumption; taxation; value added tax; customs and excise duties; goods and services